How distinct are intuition and deliberation? An eye-tracking analysis of instruction-induced decision modes - Nina Horstmann; Andrea Ahlgrimm; Andreas Glöckner (Max Planck Institute for Research on Collective Goods, 2009)
In recent years, numerous studies comparing intuition and deliberation have been published. However, until now relatively little is known about the cognitive processes underlying the two decision modes. Therefore, we analyzed processes of information search and integration using eye-tracking technology. We tested hypotheses derived from dual-process models which postulate that intuition and deliberation are completely distinct processes against predictions of interventionist models. The latter assume that intuitive and deliberate decisions are based on the same basic process which is supplemented by additional processes in the deliberate decision mode. We manipulated decision mode between-participants by means of instructions and participants completed simple and complex city-size tasks as well as complex legal inference tasks. Our findings indicate that the instruction to deliberate does not necessarily increase levels of processing. We found no difference in mean fixation duration and the distribution of short, medium and long fixations. Instruction-induced deliberation led to a higher number of fixations, a more complete information search and more repeated information investigations. Overall, the data support interventionist models suggesting that decisions mainly rely on automatic processes which are supplemented by additional operations in the deliberate decision mode.
Keywords: 610; Decision Making; Decision Mode; Intuition; Deliberation; Eye-Tracking; Entscheidung; Entscheidung bei Risiko; Informationsverhalten; Kognition; Test